Arabic Game Training for Aisyiyah Bustanul Athfal Kindergarten Teachers - Miatin Rachmawati; Ai Fatimah Nur Fuad; Fitria Nugrahaeni (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Community service activities are one of the four pillars of Muhammadiyah higher education which must be carried out by lecturers. Community service in this case is the "Al-Ab Alughowi" Arabic Game Training for Kindergarten Teachers "Aisyah Bustanul Athfal. The purpose of this activity is to increase the skills of kindergarten teachers in learning Arabic and to make Arabic learning teaching. This community service partner is the Kindergarten Teachers "Aisyah Bustanul Athfal" in Sukmajaya Depok District, while this activity is to provide training on Al-Ab Al-Lughowi. The result of this activity is that the training is carried out with 3 things, First: namely the procedures for language games, Second: discussion of the benefits of games for kindergarten children. Third: is the game practice by Aisyah Bustanul Athfal Kindergarten teachers. This training helps Arabic teachers to be creative and innovative in teaching Arabic at school. The results of this activity are expected to increase understanding of Arabic language games specifically for Aisyah Bustanul Athfal Kindergarten teachers to become additional skills for teachers. Keywords: Training, Kindergarten teachers, Arabic Game.